Technology Company Merger and Acquisition: a Study of Indonesian and European Union Competition Law - Reni Budi Setianingrum; Mukti Fajar Nur Dewata; Rahul Kumar (Fakultas Hukum Universitas Muhammadiyah Magelang, 2023)
Technology has become an essential part of human activities, people's needs and demands for it are significantly increased. People have become dependent on technology because they use it to travel, communicate, learn, do business and simplify human life. Currently, technology-based companies are growing rapidly all over the world, as we can see how Google, Facebook, Twitter, Microsoft, Apple, and various other companies dominate the market. Likewise in Indonesia, people's activities cannot be separated from various products from technology-based companies, such as Gojek, Tokopedia, Shopee, Grab, Traveloka, etc. Recently, Gojek and Tokopedia officially merged to become the GoTo Group and are claimed to be the largest technology group in Indonesia. This merger is usually carried out by business actors to seek more profit and to become a company that wins the market both on a national and international scale and in fact has a significant impact on changes in structure and control over the market so that there is a potential for abuse of dominant position to occur by limiting the choice of both products, quality, and price. Based on this case, this normative research using the case approach and statute approach aims to analyze how Indonesian competition law regulates technology company mergers, by comparing it with European Union competition law. The conclusion of this research is, lesson learn from European Union, Indonesian Competition Law needs to adapt the Data Protection Law in reviewing tehcnology company mergers in Indonesia.